We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
254
1
avatar+4322 

If \(f(x)=x^3+3x^2+3x+1\), find \(f(f^{-1}(2010))\)

 Mar 11, 2018

Best Answer 

 #1
avatar+18957 
+1

f (f^-1 (x) )  = x        = 2010

 Mar 11, 2018
 #1
avatar+18957 
+1
Best Answer

f (f^-1 (x) )  = x        = 2010

ElectricPavlov Mar 11, 2018

37 Online Users

avatar
avatar